Windows forensics cookbook : 61 recipes to help you analyze Windows systems - Sulkin, Oleg; Courcier, Scar de (Packt Publishing, 2017)
Maximize the power of Windows Forensics to perform highly effective forensic investigations About This Book Prepare and perform investigations using powerful tools for Windows, Collect and validate evidence from suspects and computers and uncover clues that are otherwise difficult Packed with powerful recipes to perform highly effective field investigations Who This Book Is For If you are a forensic analyst or incident response professional who wants to perform computer forensics investigations for the Windows platform and expand your took kit, then this book is for you. What You Will Learn Understand the challenges of acquiring evidence from Windows systems and overcome them Acquire and analyze Windows memory and drive data with modern forensic tools. Extract and analyze data from Windows file systems, shadow copies and the registry Understand the main Windows system artifacts and learn how to parse data from them using forensic tools See a forensic analysis of common web browsers, mailboxes, and instant messenger services Discover how Windows 10 differs from previous versions and how to overcome the specific challenges it presents Create a graphical timeline and visualize data, which can then be incorporated into the final report Troubleshoot issues that arise while performing Windows forensics In Detail Windows Forensics Cookbook provides recipes to overcome forensic challenges and helps you carry out effective investigations easily on a Windows platform. You will begin with a refresher on digital forensics and evidence acquisition, which will help you to understand the challenges faced while acquiring evidence from Windows systems. Next you will learn to acquire Windows memory data and analyze Windows systems with modern forensic tools. We also cover some more in-depth elements of forensic analysis, such as how to analyze data from Windows system artifacts, parse data from the most commonly-used web browsers and email services, and effectively report on digital forensic investigations. You will see how Windows 10 is different from previous versions and how you can overcome the specific challenges it brings. Finally, you will learn to troubleshoot issues that arise while performing digital forensic investigations. By the end of the book, you will be able to carry out forensics investigations efficiently. Style and approach This practical guide filled with hands-on, actionable recipes to detect, capture, and recover digital artifacts and del ...